Choral Societies and Nationalism in Europe (Volume 9) - Stynen, Andreas; Lajosi, Krisztina (Brill, 2015)
This wide-ranging contribution to the study of nationalism and the social history of music examines the relationship between choral societies and national mobilization in the nineteenth century. From Norway to the Basque country and from Wales to Bulgaria, this pioneering study explores and compares the ways choral societies influenced and reflected the development of national awareness under differing political and social circumstances. By the second half of the nineteenth century, organized communal singing became a primary leisure activity that attracted all layers of society. Though strongly patriotic in tone, choral societies borrowed from each other and relied heavily on prominent German or French models. This volume is the first to address both the national and transnational significance of choral singing. Contributors are: Carmen De Las Cuevas Hevia, Jan Dewilde, Tomáš Kavka, Anne Jorunn Kydland, Krisztina Lajosi, Joep Leerssen, Sophie-Anne Leterrier, Jane Mallinson, Tatjana Marković, Fiona M. Palmer, Karel Šima, Andreas Stynen, Dominique Vidaud, Ivanka Vlaeva, Jozef Vos, Gareth Williams, Hana Zimmerhaklová.